Morphology and thermoluminescence properties of terbium doped magnesium orthosilicate. (April 2017) - Zhao, Y.; Wang, Y.; Cui, M.; Jin, H.; Fan, Z.; Zhao, C.; Wu, X.; Townsend, P.D.
Abstract: The morphology and structural form of Tb doped magnesium silicate are reported as a function of the dopant concentration of Tb. The preparation method is described. This includes a sintering step which is time sensitive and an optimum processing time is discussed to improve dosimeter sensitivity. The thermoluminescence spectra are remarkable as they reveal peak shifts in the temperature of the characteristic lines of the Tb dopant. A model related to charge capture by different upper state orbitals of the rare earth transitions is offered. Optically stimulated luminescence data are also included. Highlights: Thermoluminescence spectra of terbium doped Mg2 SiO4 are reported. Glow peak shifts of the characteristic lines of terbium are reported. A model related to charge capture by different upper state orbitals of the rare earth transitions is offered.